E-payment development: The adoption of E-payment among undergraduates in Malaysia - Chin, Yen Jie; Tan, Eunice Xin Yu; Kam, Kai Yi; Loh, Zhi Hui (2025)
E-payment methods have been increasingly popular in recent years, particularly among younger generation. Knowing what influences undergraduate students’ use of electronic payments is becoming progressively more important as digital technologies continue to change the financial environment. With a focus on four main variables which are perceived security, perceived benefit, social influence, and worries about counterfeit currency. This study attempts to explore the major factors influencing Malaysian undergraduate students’ adoption of electronic payments. A cross-sectional survey design was employed to obtain primary data from 400 undergraduate students from Malaysia’s public and private institutions. Convenience sampling was used, and data was collected via a standardized questionnaire delivered on both physical and digital channels. The instrument included demographic questions as well as measuring items for the four independent variables, all of which were graded on a five-point Likert scale. A pilot test with 50 respondents was undertaken to confirm that the survey items were clear and reliable. Cronbach’s Alpha was used to verify the construct’s internal consistency, and all variables met the acceptable threshold of 0.70. The findings of this study are likely to provide useful insights into how undergraduates perceive and interact with e-payment platforms. Understanding these perspectives will help to fill in the gaps in past study on e-payment uptake and the promotion of a cashless society, as well as the actual user behavior of young customers. The conclusions will also include recommendations for financial institutions and fintech companies to improve security, enhance user experience, and raise awareness about the benefits of digital payments. Finally, this study contributes to Malaysia’s digital economy goals by proposing solutions that promote higher e-payment use and financial inclusion among Malaysian undergraduates. Keywords: UTAUT model; Malaysia undergraduates; counterfeit currency; cybersecurity; electronic payment adoption; convenience Subject Area: HG1710-1710.5 Electronic funds transfers